Demographic and Economic Center of Gravity of Nepal - Maharjan, Milan; Subedi, Sandu (Journal of Economics Students, 2023)
In this paper, an attempt has been made on determination of the Demographic Center of Gravity (DCG) and Economic Center of Gravity (ECG) of Nepal The results are then used for the study of historical demographic dynamics and present spatial heterogeneity in distribution of population and economic activities across the country. Census data from 1971-2021 shows the net shift of DCG of Nepal by about 12.5 km toward South-West direction with location in 2021 being at 84.588°E 27.648°N, Khairhani Municipality, Chitwan. Likewise, the ECG of Nepal in FY 2020/21 was at 84.780°E 27.655°N, near the tri-junction point of Chitwan, Makawanpur and Dhading districts. Due to unavailability of enough historical data of Provincial Gross Domestic Product (PGDP), the historical shift in ECG couldn’t be traced. Besides this, the Geographic Centroid (GC) of Nepal is estimated being at 83.920°E 28.277°N, Pokhara, Kaski. From these findings, it is seen that the DCG and ECG lie towards the South-East of GC of Nepal suggesting that the population and economic activities of Nepal is more concentrated on the southern Terai part of Nepal than Hills and inclined toward Eastern part of Nepal than the West.